OBSERVASI PENYIMPANAN OBAT DI APOTEK KIMIA FARMA ABIAN TUBUH PADA TAHUN 2023 - Annisa, Janatul; Saputra, Yoga Dwi (Fakultas Farmasi UMI, 2024)
One of the place that offers health services is a pharmacy, especially leading to pharmaceutical practice. A series of drug treatment and storage is carried out by putting the medicine in a protected place. One of the factors that affecting the quality of medicine is how well it is stored. Objective of this study was to observe and assess the drug storage system of 7 different therapeutic classes at Kimia Farma Abian Tubuh Pharmacy with the aim of improve pharmaceutical services provided by pharmacies as stipulated in the Regulation of the Minister of Health of the Republic of Indonesia Minister of Health of the Republic of Indonesia Number 73 of 2016 and Regulation of the Minister of Health No. 9 of 2017 concerning Apothecaries. Health Minister Regulation No. 9 of 2017 concerning Pharmacies. Information gathering is carried out by direct perception of the system through in-depth interviews with pharmacists and observation sheets. The observation results show that the level of drug storage at Kimia Farma Abian Tubuh Pharmacy is “96.67% Very Good” (81-100%) which indicates that storage at the pharmacy has been Good” (81-100%) which shows that storage at the pharmacy is in accordance with the guidelines. according to the guidelines